Animal Classification Using Appearance-Based, Model-Based and Texture-Based Methods - Othman, Shaafan Jameel (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
Animal recognition and their classification have become increasingly popular area in pattern recognition and computer vision. Distinguishing between images of different animals and different species as means of classifying animals is an easy task for humans. However, it is difficult to distinguish animal species automatically even in simple cases such as distinguishing cats and dogs. Animal bodies easily get disfigured, they can appear in images in a way that they self-occlude and often the background in such images could be very complex and noisy. Furthermore, just as all objects in an image, illumination may vary from image to image, the dimension and viewpoints may also differ. There has been attempts to carry out animal recognition from images but this problem has gained not enough attention. In the literature, there are some visual animal biometrics algorithms categorizing specific animal species such as zebra, elephant, chimpanzees, tiger, whales, pet animals like dogs, etc. Moreover, there are a few publicly available animal face databases including the facial images of different animals such as LHI Animal Faces, HiT and KTH Databases. In this thesis, we studied on different animal face images to classify different animal species. We implemented appearance-based, texture-based and model-based feature extraction methods to categorize animals from their faces and a comparative study is performed at the end of the thesis. Keywords: Animal classification, visual animal biometrics, appearance-based methods, model-based methods, texture-based methods.

ÖZ: Hayvan türlerinin sınıflandırılması ve hayvan tanıma, bilgisayarla görü ve örüntü tanıma alanlarında önemli bir uygulamadır. Hayvan sınıflandırma, değişik hayvan türü görüntülerinin ayırt edilmesi problemini çözmek için kullanılır. Bu problem insanlar için basit bir iş olsa da, bilgisayarla otomatik olarak, kedi ve köpekleri bile ayırt etmek zordur. Hayvanların vücutları deforme olup kendi kendini kapatma veya saklama özelliğine sahiptir ve bu işlem karmaşık arkaplan görüntüleriyle daha da belirgin hale gelir. Bunlara ek olarak, bütün nesneler gibi hayvanlar da farklı ışıklandırılmış, farklı görüş açısıyla ve farklı büyüklükte görünebilir. Hayvan görüntüleri üzerinde tanıma yöntemlerini uygulamak için girişimler yapılmış, ancak hayvanların kategorize edilmesi problemi üzerinde çok yaygın çalışmalar yapılmamıştır. Literatürde bazı görsel biyometri algoritmaları kullanılıp, zebra, fil, şempanze, kaplan, balina, köpek gibi bazı hayvan türlerinin sınıflandırılması yapılmıştır. Ayrıca, LHI Hayvan Yüzleri, HiT ve KTH veritabanları gibi sınırlı sayıda halka açık hayvan görüntüsü veritabanı bulunmaktadır. Bu tezde, değişik hayvan türlerinin sınıflandırılması için hayvan yüzü görüntüleri üzerinde çalışılmıştır. Görüntüye-dayalı, dokuya-dayalı ve modele-dayalı öznitelik çıkarma yöntemleriyle hayvan yüzlerinin sınıflandırılması yapılmıştır. Bu yöntemlerin hayvan sınıflandırma problemi üzerindeki başarımları tezin sonunda karşılaştırılmıştır. Anahtar kelimeler: Hayvan sınıflandırma, görsel hayvan biyometrisi, görüntüye-dayalı yöntemler, modele-dayalı yöntemler, dokuya-dayalı yöntemler.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2018. Supervisor: Assoc. Prof. Dr. Önsen Toygar.
Keywords: Computer Engineering; Animal--Classification; Pattern perception; Animal classification; visual animal biometrics; appearance-based methods; model-based methods; texture-based methods